Barriers to Dietary Compliance among Diabetic Patients - Hanady Jabbar Mahmood (Iraqi National Journal of Nursing Specialties, 2023)
The aim of the study is to identify the barriers to dietary compliance among diabetic patients. Methodology: The sample of the study consist of 100 patients who were divided into two groups according to the type of diabetes mellitus; type 1 (Insulin-dependent diabetic mellitus), and type n (Non-Insulin dependent diabetes mellitus). Each group consists of 50 patient selected randomly at each visit to Al-Waffa center in Mosul city during the period from (1-12-2005) to (1-2-2006). The steps of the study include recording the different barriers for diabetic patients. The questionnaire was used and special list was utilized for such purpose. Results: The results shows that there were some barriers most common such as bothering of diet, not believe in diet therapy, dependent of the drugs of diabetic, and lack of knowledge about diabetic diet and shows the lest common barriers such as social barriers, unable to control himself from «»ting and another barriers. Recommendations: The suggestion to undertake teaching about the complications of diabetes or other diabetesrelated health problems health education by means of pamphlets, booklets new paper and television what can help in minimizing the barriers of diet and compliance of diabetes mellitus.